Catalog of the type specimens of Gelechioidea (Lepidoptera) in the collection of the National Museum of Natural History, Smithsonian Institution, Washington, DC - Brown, John W.; Adamski, David; Hodges, Ronald W.; Bahr, Stephen M. (Zootaxa, 2004)
The collection of the National Museum of Natural History, Smithsonian Institution, Washington, D.C., is second only to that of The Natural History Museum (formerly British Museum of Natural History), London, in the number of type specimens of the superfamily Gelechioidea (Lepidoptera). The Smithsonian houses 1,375 gelechioid types: 1,249 holotypes, 48 lectotypes, 1 neotype, 69 species represented by one or more syntypes, and 8 species represented by one or more “pseudotypes” (i.e., specimens identified as “type” by an accompanying label that are unlikely to be the type). Three former curators are responsible for the vast majority of the type specimens: August Busck, J. F. Gates Clarke, and Ronald W. Hodges. We present a list of the species for which a type is deposited in the USNM, organized alphabetically. For each species we provide an abbreviated reference to the original description and label data. This list represents the second contribution to a larger effort to make available information on the Lepidoptera type holdings of the USNM.